Nuit sur حاج فاتح (Haj Fateh) : à la découverte de territoires psychiques méconnus de l’occident - Elise Defrasne Ait-Said (Bollettino della Società Geografica Italiana)
It is at nightfall that the metamorphosis of the Haj Fateh working-class district in Casablanca takes place. The author recounts the succession of events that take place there, in their most lively and positive aspects, sometimes also disconcerting. The characteristics of this neighbourhood urban planning seem to be perfectly combined with the movements of human nightlife. The interpretation of certain behaviours is approached in the light of beliefs and representations specific to Islamic culture. This is how we will walk from nightfall to dawn, among the human figures of this Moroccan district, and accompanied by these invisible beings, the djinns, with their rhythms and their unveilings.